2012
DOI: 10.1080/00221325.2011.594820
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, Parenting, and Separation–Individuation in Adolescence: A Comparison of Hospitalized Adolescents, Institutionalized Delinquents, and Controls

Abstract: The authors compared parent-related perceptions by hospitalized adolescents (i.e., who were admitted to a specialized psychiatric unit; n = 50) and delinquent adolescents (i.e., who were placed at a juvenile treatment institution; n = 51) with adolescents from the general population (n = 51). All adolescents completed a broad set of measures of attachment, perceived parenting, and separation-individuation. Contrary to initial expectations, hospitalized adolescents scored higher than controls on indices of exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…There are likely many factors that account for the variability in different aspects of individuation, so it would be idealistic to expect even moderate relationships of these variables with individuation. We propose that there may be other individual factors that would explain a larger amount of variability in emerging adults' individuation, e.g., personality (Zupančič & Kavčič, 2014), coping strategies (Luyckx, Klimstra, Duriez, Scheartz, & Vanhalst, 2012), and relationship factors such as security of parent–child attachment (Delhaye, Kempenaers, Burton, et al., 2012) and perceived quality of parenting (Delhaye, Kempenaers, Linkowski, et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are likely many factors that account for the variability in different aspects of individuation, so it would be idealistic to expect even moderate relationships of these variables with individuation. We propose that there may be other individual factors that would explain a larger amount of variability in emerging adults' individuation, e.g., personality (Zupančič & Kavčič, 2014), coping strategies (Luyckx, Klimstra, Duriez, Scheartz, & Vanhalst, 2012), and relationship factors such as security of parent–child attachment (Delhaye, Kempenaers, Burton, et al., 2012) and perceived quality of parenting (Delhaye, Kempenaers, Linkowski, et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This finding may reflect the Slovene family context that can be characterized by an on-going instrumental assistance of parents to their emerging adult children. However, as shown by some studies on emerging adulthood in Western European countries (e.g., Delhaye, Kempenaers, Burton, et al, 2012;Seiffge-Krenke, 2006), such family contexts (usually found in Southern European countries) might be becoming a more common pattern of family functioning during the transition to adulthood.…”
Section: Limitations Strengths and Conclusionmentioning
confidence: 96%
“…Many studies were not based on a general population sample, instead focusing on specific groups, such as criminal offenders (Schimmenti 2014;Lahlah 2013;Kimonis 2013;Simons 2008;Wileman 2008;Palmer 2007;Kiriakidis 2006). Eleven studies evaluated both male and female participants (Schimmenti 2014;Nunes 2013;van der Voort 2013;Delhaye 2012;Sousa 2011;Ingoglia 2011;Johnson 2011;Hiramura 2010;Day 2009;Tyler 2006;Heaven 2004), whereas six studies exclusively evaluated male participants (Lahlah 2013;Kimonis 2013;Simons 2008;Wileman 2008;Palmer 2007;Kiriakidis 2006). Most studies were quantitative; however, some studies employed a cross-sectional (Nunes 2013;Lahlah 2013;Kimonis 2013;Delhaye 2012;Ingoglia 2011;Hiramura 2010;Day 2009;Simons 2008;Palmer 2007;Kiriakidis 2006;Heaven 2004) or longitudinal design (van der Voort 2013;Sousa 2011;Johnson 2011;Tyler 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Similar experiences of detachment were also identified in several of the reviewed studies. For instance, Delhaye et al (2012) reported that delinquent youth scored significantly higher on measures of detachment, suggesting a conflictual and radical form of distancing from parents, including distrust and perceived alienation. Similarly, Ingoglia et al (2011) found that adolescents with parental detachment tended to report higher levels of aggressive and disruptive behavior.…”
Section: Emotional Carementioning
confidence: 99%
“…Risk factors include lack of parental monitoring or inept discipline, poor family functioning, maltreatment, low family affection and warmth, and parental problems such as drug (ab)use, psychopathology, and criminal activity [ 6 , 21 , 33 , 47 ]. If the family of the delinquent adolescent is not given appropriate attention, poor family functioning is likely to persist, influencing the prospect of the youth to get involved in the juvenile justice system [ 8 , 9 , 20 , 34 ].…”
Section: Introductionmentioning
confidence: 99%